Evaluation of Changes in the Scale and Direction of Thermal Pollution Flows in the Kalinin NPP Cooling Lakes From 1985 to 2020 - Bocharov A. V.; Lebedev Sergey; Kravchenko P. N. (Russian Journal of Earth Sciences, 2023)
The article evaluates the change in the scale and direction of thermal pollution flows of the cooling lakes of the Kalinin NPP from 1985 to 2020 based on the use of Earth remote sensing data. A retrospective analysis was carried out using satellite images obtained by the sensors of the Landsat series satellites. An analysis of the distribution of surface water temperature over the water area of NPP cooling lakes has been carried out. The change in the structure of thermal pollution after the increase in the capacity of the Kalinin NPP is determined. The temperature of the cooling lakes of the Kalinin NPP was estimated relative to the background indicators in the lakes-analogues, which were used as nearby Lake Navolok and Lake Kezadra. The study identified five stages of transformation of the water mass circulation system in the cooling lakes of the Kalinin NPP.